EFFECT OF CHEMICAL MEDIA COMPONENTS AND SILVER NANOPARTICLES ON THE INDUCTION OF CALLUS CULTURE AND ACCUMULATION OF SECONDARY COMPOUNDS IN A Trigonella foenum-graecum L. - Masara D. J.,; S. I. Neamah, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was investigate the effect of components media and silver nanoparticles (Ag-NPs) synthesized in the laboratory on the induction of biomass and secondary metabolites  of calli cultures induced from the cotyledons of Trigonella foenum-graecum L. The culture media LS and B5 were tested with the growth regulators 2,4-Dichlorophenoxyacetic acid (2,4-D) at a concentration of 1.0, 2.0 and 3.0 mg l-1 and 6-benzyladenine (BA) at a concentration of 0.0, 0.5, 1.0, 1.5 and 2.0 mg l-1, with the aim of studying its effect on callus induction. In comparison, Ag-NPs were used at a concentration of 0.0, 0.5, 1.0, 1.5 and 2.0 mg l-1 to study its effect on the production of some secondary compounds. The results showed that the mixture consisting of the culture media LS with 3.0 mg l-1 of 2,4-D and 1.0 mg L-1 of BA the highest percentage of callus induction and the minimum days to complete callus formation. While, the same media with 2.0 mg l-1 2,4-D and 1.0 mg l-1 of BA recorded the highest dry weight (DW) and relative water content (RWC). The combination B5×2.0 mg l-1 2,4-D×1.5 or 2.0 mg l-1 showed the highest fresh weight (FW) and the lowest time required to start callus induction, respectively. As for the production of SC, the B5 media with 2.0 mg l-1 of Ag-NPs achieved the highest concentration of alkaloid compounds represented by trigonelline and diosgenin, and flavonoids expressed by qurcetine, vitxein, rutin, apigenin, isovitexin, and kaemferol.